The Role of Statistic Information in the Information Society - Gerasymenko, S. S. (Statistics of Ukraine, 2020)
The article is dedicated to substantiation of the leading role of the necessity to understand and to apply the main propositions of statistics in scientific society with the aim to ensure its progressive development. In order to substantiate the currency of the solution of this questions there were considered the contradictions occurred in connection with the divergences in understanding the basic concepts, which are very often used by the society, in particular the concert “information”. Very often the concept “data” is replaced by the concept “information” that becomes in many cases the reason for appearance of incorrect terms. It was also noted the insufficient level of statistic competence of the society as to the possible character of any phenomena and processes, in the Universe and in the society, the results of which according to the results of observation, very often become false at all or mistaken conclusions. In particular, using the statistic approach the main conclusions, defined by some scientists-physicists in XX century were considered. It was proved that very often these conclusions were made without taking into account the possible character of all phenomena and processes that take place in the Universe. It’s stressed, that applying the statistic principles as for the collecting the data and creating the useful for making the decision information so for defining the conclusions according to the results of the analysis and prognostication of the phenomena and processes favours the higher of substantiation of managerial decisions. It was pointed to the drawbacks of the set of number, that make the so-called “modern sources of information” – Big Data, Business intelligence, Data mining, Smart-society, in the case of their usage for characterizing the social-economic phenomena and processes. The proposition was made about the necessity to gain the practical knowledge in statistics by all the persons who have to define the conclusions according to the results of observation of the objects and phenomena and also to develop the steps with the aim of their further changes. So while making the prognosis of social-economic phenomena and processes it is obligatory to take into consideration the main regularity of development – cyclicality. There were generalized statistic recommendations as to the forming the statistic information, the application of which will favour to higher the efficiency of the process of creating such information, which in its turn, will become the weighty factor of acceleration of the modern information society.